Uang Tidak Berkuasa: Bukti Baru dari Pemilihan Kepala Daerah di Indonesia - Mohammad Hidayaturrahman; Ahmad Hasan Ubaid; Puguh Wiji Pamungkas; Anak Agung Putu Sugiantiningsih (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
Many studies have shown that money has power in political contestation in Indonesia, including research by Burhanuddin Muhtadi, Edward Aspinall, and others. This research finds the opposite: money does not confer power in political contestation in Indonesia. This is based on findings from regional head elections held simultaneously across 270 regions in Indonesia for the 2020-2025 period. Sixty business actors are running as candidates for regional heads and their deputies. Of this number, only 17 business pairs were regional head candidates and won the contest, or 28.3 percent. Forty-three candidate pairs from business backgounds lost the election, representing 71.7 percent of the total. This is relevant to the Kompas survey conducted in July 2020, which showed that 69.4 percent of voters did not pay attention to the money politics distributed by the candidates. Voters still receive the money distributed but vote according to their conscience. Money is not the main factor that determines the victory of a regional head candidate. There are many other factors, such as communication and the closeness of regional head candidates to voters. This research uses analytical qualitative methods, and data collection is carried out by searching for documents in trusted online media, both national and local. It would be no less attractive if further research examined whether the involvement of business actors in regional head elections is more successful when they become political investors or direct candidates.